CASE BASED LEARNING INNOVATIONS OF ENVIRONMENTAL MANAGEMENT - Fenty Fauziah; Fitriansyah Fitriansyah; Bambang Sutedjo; Muhammad Said (JURNAL PAJAR (Pendidikan dan Pengajaran), 2022)
Case Based Learning (CBL) is learning that is oriented towards effective and interesting problem solving, discussions of specific situations and examples of real events in the business world. The object of the case used is an effort to preserve the environment that affects the business world from an economic, social, political and legal perspective. The activity was carried out at Sungai Karang Mumus School (SKM School), which is located on Jalan Muang Ilir, Betapus Village, Samarinda. This study aims to analyze the effect of the application of CBL on the motivation of student learning outcomes. The study used a pre-post-test approach. The total population is 25 students of Master of Management, University of Muhammadiyah East Kalimantan who are members of the environmental management class and use the total sampling technique. Non-parametric statistics, namely the pairing test of the Paired Sample t-test with the Wilcoxon test used in data processing. The results showed that there was a significant difference in student motivation and learning outcomes before applying case-based learning methods and before case-based learning was applied to environmental management courses. Students who are looking to study will have good learning outcomes. Students and then get used to think critically and use prior knowledge in problem solving. This has triggered educators and institutions to apply case-based learning methods as innovative learning.